2015
DOI: 10.1021/acs.inorgchem.5b01994
|View full text |Cite
|
Sign up to set email alerts
|

Spontaneous Resolution of Evans–Showell-Type Polyoxometalates in Constructing Chiral Inorganic–Organic Hybrid Architectures

Abstract: Six new hybrid compounds based on [Co2Mo10H4O38](6-) polyoxoanion, (4-H2pya)6Co2Mo10H4O38·10H2O 1 (4-Hpya =3-(4-pyridyl)acrylic acid) and (4-H2pya)4[M(H2O)6][Co2Mo10H4O38]·5H2O (M = Co 2, Ni 3, Cu 4, Zn 5, Cd 6), were synthesized and characterized by elemental analysis, IR spectroscopy, TG analysis, solid diffuse reflective spectrum, powder X-ray diffraction, and single crystal X-ray diffraction. Compound 1 crystallizes in the centrosymmetric space group P-1, which is built up of protonated 4-H2pya molecules a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

3
16
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 32 publications
(19 citation statements)
references
References 62 publications
(116 reference statements)
3
16
0
Order By: Relevance
“…The second approach to assemble chiral POM-based hybrid materials is based on self-assembly by the change of bond distances and bond angles, the formation of lacunae, structure transformation, substitution with other metals, or modification with an achiral structural unit to destroy the mirror or symmetric centers. In this situation, chiral POM-based hybrid materials can be isolated in enantiomerically pure form by spontaneous resolution. It is very rare for spontaneous resolution phenomena and only happens occasionally. …”
mentioning
confidence: 99%
“…The second approach to assemble chiral POM-based hybrid materials is based on self-assembly by the change of bond distances and bond angles, the formation of lacunae, structure transformation, substitution with other metals, or modification with an achiral structural unit to destroy the mirror or symmetric centers. In this situation, chiral POM-based hybrid materials can be isolated in enantiomerically pure form by spontaneous resolution. It is very rare for spontaneous resolution phenomena and only happens occasionally. …”
mentioning
confidence: 99%
“…Similar to chiral MOFs, chiral POMs [69,[91][92][93][94] have been also developed as a type of increasingly important NLO materials. [95][96][97][98] One effective method to obtain hybrid POMs with second-order NLO response is to introduce organic molecules with chiral centers. [99] In these compounds, POM might act as an electron acceptor and the organic substrate serves as a donor to generate a second-order NLO hyperpolarizability.…”
Section: Chiral Porous Materials For Second-order Nlomentioning
confidence: 99%
“…These non‐covalent interactions affect the crystal packing and the specific properties of materials . Organic cations such as viologen ( N , N ′‐disubstituted‐4,4′‐bipyridine), 1,4‐diazabicyclo[2,2,2]octane (dabco), piperazine (pip), and pyridyl were used as building blocks to assemble hybrid materials, and for the preparation of N‐containing organic cations by in situ N‐alkylation in the presence of metal salts, alcohols and strong acids. However, it is rarely reported that alcohols instead of halogenated hydrocarbons can act as alkylation reagents for organic amines …”
Section: Introductionmentioning
confidence: 99%